2009
DOI: 10.1017/s0007114509991966
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of coffee, green tea, oolong tea, black tea, chocolate snacks and the caffeine content in relation to risk of diabetes in Japanese men and women

Abstract: Although the inverse association between coffee consumption and risk of diabetes has been reported numerous times, the role of caffeine intake in this association has remained unclear. We evaluated the consumption of coffee and other beverages and food containing caffeine in relation to the incidence of diabetes. The study participants were 5897 men and 7643 women in a community-based cohort in Takayama, Japan. Consumption of coffee, green tea, oolong tea, black tea and chocolate snacks were measured with a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 34 publications
(35 reference statements)
6
92
1
1
Order By: Relevance
“…A recent meta-analysis reported that one cup of coffee per day contributed to a 7% decrease in the risk of type 2 diabetes (relative riskZ0.93; 95% CIZ0.91-0.95) (7). In addition, similar associations were observed for Asian populations (9,10,11,12). Most of these studies have demonstrated inverse associations between coffee intake and the risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 80%
“…A recent meta-analysis reported that one cup of coffee per day contributed to a 7% decrease in the risk of type 2 diabetes (relative riskZ0.93; 95% CIZ0.91-0.95) (7). In addition, similar associations were observed for Asian populations (9,10,11,12). Most of these studies have demonstrated inverse associations between coffee intake and the risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 80%
“…Later studies have mostly supported a protective association between cocoa or chocolate consumption and a variety of health indicators. These include total and cardiovascular mortality, serum C-reactive protein, psychological well-being, and risk of diabetes, myocardial infarction, and/or stroke (30,59,116,189,236).…”
Section: Katz Et Almentioning
confidence: 99%
“…Usually, the human body lacks of antioxidants and become susceptible to damage by free radicals. Flavonoids from cocoa have antioxidant qualities on vascular health, lowering the blood pressure, improving the blood flow to the brain and heart, making the blood platelets less sticky and preventing the clotting [14,[15][16][17][18][19][20][21]23]. Beside the cocoa, the flavonoids are found in variety beverages like tea, peanuts, apples, onions, cranberries and red wine.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of flavonoids have been extensively studied, results of reviews and meta-analyses supporting the positive role of cocoa on blood pressure by increasing the formation of endothelial nitric oxide involved in vasodilatation, on cholesterol levels, on atherosclerosis and insulin resistance [14,[15][16][17][18][19][20][21]. Still, it remains unclear whether chocolate consumption is related to reductions in hard cardiovascular outcomes (such as myocardial infarction and stroke) or has just an intermediate effect on cardiometabolic disorders.…”
Section: Introductionmentioning
confidence: 99%